تحليل تعليم اللغة العربية في المدون المصغر لإنستغرام "عربية تلكس" على ضوء المدخل الاتصالي - Sujefri, Alfan (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2022)
Learning material is an important thing in learning Arabic. In this era, learning materials are modified into a more modern form. One of them is the use of Instagram as an Arabic learning microblog. The Instagram microblog is equipped with audiovisuals that support the presentation of Arabic learning materials, especially maharah kalam. The relevant Maharah kalam learning uses a communicative approach. However, in the Instagram microblog, there are still various problems when presenting material and forms of evaluation related to the communicative approach. This was found on the Instagram microblog arabiyahtalks which presents Arabic learning materials but there are still some obstacles. From there, the objectives of this study are as follows: 1) To describe the presentation of Arabic learning materials for microblog instagram arabiyahtalks from the perspective of a communicative approach, and 2) To describe the evaluation of learning materials for Arabic microblog instagram arabiyahtalks from the perspective of a communicative approach. In this study, the researcher used a qualitative method and the type was descriptive. Because the data needed is in the form of detailed information related to the scope of the research and the researcher describes the data to the maximum. The research data collection used instruments in the form of documentation, interviews, and observations. The results of the research are as follows: 1) The material in the Instagram microblog is presented in the form of images, short videos containing explanations of Arabic learning materials designed using certain design applications. Constraints in presenting the material in the form of a lack of number of slides when presenting complex material, 2) Evaluation of material in the Instagram arabiyahtalks microblog is presented in the form of questions in the instastory and comment column. Constraints in evaluating the material in the form of no value recap because the number of followers is very large. Keywords: Learning Materials; Instagram Microblog; Communicative Approach ABSTRAK Materi pembelajaran merupakan hal yang penting keberadaanya di dalam pembelajaran bahasa Arab. Di era ini, materi pembelajaran termodifikasi ke dalam bentuk yang lebih modern Salah satunya adalah penggunaan Instagram sebagai microblog pembelajaran bahasa Arab. Microblog instagram dilengkapi audiovisual yang mendukung penyajian materi pembelajaran bahasa Arab, khususnya maharah kalam. Pembelajaran Maharah kalam relevan menggunakan pendekatan komunikatif. Namun, dalam microblog Instagram masih ditemukan berbagai permasalahan saat menyajikan materi dan bentuk evaluasi berkaitan dengan pendekatan komunikatif. Hal ini ditemukan di dalam microblog instagram arabiyahtalks yang menyajikan materi pembelajaran bahasa Arab namun masih ada beberapa kendala. Dari situ, tujuan penelitian ini sebagaimana berikut: 1) Untuk mendeskripsikan penyajian materi pembelajaran bahasa Arab microblog instagrama arabiyahtalks perspektif pendekatan komunikatif, dan 2) Untuk mendeskripsikan evaluai materi pembelajaran bahasa Arab microblog instagram arabiyahtalks perspektif pendekatan komunikatif. Pada penelitian ini, peneliti menggunakan metode kualitatif dan jenisnya deskriptif. Karena data yang dibutuhkan dalam bentuk informasi secara rinci terkait cakupan penelitian dan peneliti mendeskripsikan data tersebut dengan maksimal. Adapun pengumpulan data penelitian menggunakan instrument berupa dokumentasi, wawancara, dan observasi. Adapun hasil penelitiannya sebagai berikut: 1) Materi di dalam microblog Instagram disajikan dalam bentuk gambar, video pendek yang memuat penjelasan materi pembelajaran bahasa arab yang didesain menggunakan aplikasi desain tertentu. Kendala yang dalam penyajian materi berupa kurangnya jumlah slide saat menyajikan materi yang rumit, 2) Evaluasi materi di dalam microblog Instagram arabiyahtalks disajikan dalam bentuk pertanyaan di instastory dan kolom komentar. Kendala evaluasi materi berupa tidak adanya perekapan nilai karena jumlah followers yang sangat banyak. Kata-Kata Kunci: Materi Pembelajaran; Microblog Instagram; Pendekatan Komunikatif.